THE TRANSIENT ACCRETING X-RAY PULSAR XTE J1946+274: STABILITY OF X-RAY PROPERTIES AT LOW FLUX AND UPDATED ORBITAL SOLUTION - Marcu-Cheatham, Diana M.; Pottschmidt, Katja; Kühnel, Matthias; Müller, Sebastian; Falkner, Sebastian; Caballero, Isabel; Finger, Mark H.; Jenke, Peter J.; Wilson-Hodge, Colleen A.; Fuerst, Felix; Grinberg, Victoria; Hemphill, Paul B.; et al. (Astrophysical Journal, 2015)
We present a timing and spectral analysis of the X-ray pulsar XTE J1946+274 observed with Suzaku during an outburst decline in 2010 October and compare with previous results. XTE J1946+274 is a transient X-ray binary consisting of a Be-type star and a neutron star with a 15.75 s pulse period in a 172 days orbit with 2-3 outbursts per orbit during phases of activity. We improve the orbital solution using data from multiple instruments. The X-ray spectrum can be described by an absorbed Fermi-Dirac cut-off power-law model along with a narrow Fe K alpha line at 6.4 keV and a weak Cyclotron Resonance Scattering Feature (CRSF) at similar to 35 keV. The Suzaku data are consistent with the previously observed continuum flux versus iron line flux correlation expected from fluorescence emission along the line of sight. However, the observed iron line flux is slightly higher, indicating the possibility of a higher iron abundance or the presence of non-uniform material. We argue that the source most likely has only been observed in the subcritical (non-radiation dominated) state since its pulse profile is stable over all observed luminosities and the energy of the CRSF is approximately the same at the highest (similar to 5 x 10(37) erg s(-1)) and lowest (similar to 5. x 10(36) erg s(-1)) observed 3-60 keV luminosities.
Keywords: accretion; accretion disks; pulsars: individual (XTE J1946+274); X-rays: binaries